STRATEGI PEMBELAJARAN FIQIH JINAYAT MELALUI METODE DOSCUSSION GRUP DAN IMPLIKASINYA DI MADRASAH ALIYAH AL-HIKMAH KEDIRI - Hazballoh, Muhammad (Mozaic: Islamic Studies Journal, 2024)
This study aims to analyze the teaching strategies for Fiqh Jinayat implemented through the discussion group or Musyawarah method at Madrasah Aliyah Al-Hikmah Kediri, along with its implications for the learning process and outcomes. The discussion group method was selected as an interactive approach to enhance students' comprehension of the complex and critically analytical subject matter of Fiqh Jinayat. A descriptive qualitative approach was employed in this research, utilizing observation, interviews, and documentation as data collection techniques. The results demonstrate that the discussion group method creates an engaging and participatory learning atmosphere, improves students' critical thinking skills, and strengthens their understanding of Fiqh Jinayat concepts. Furthermore, this method facilitates a comprehensive grasp of the material, encourages in-depth exploration of specific topics, fosters collaboration, grants students the freedom to express their ideas, trains them to address problems confidently, and enhances their communication skills. However, the method also presents challenges, including consuming significant time and heavily depending on vocal students to sustain discussions. The study concludes that the discussion group method is an effective strategy for teaching Fiqh Jinayat, particularly within the educational context of Madrasah Aliyah.